Access to Dental Providers in Pennsylvania Exploration of the County-Level Distribution of Dental Providers and Populations in 2013 - Baird, Matthew D. (RAND Corporation, 2016)
This report examines an important factor in the ability to access dental care: the distribution and availability of dental health providers. The authors assess these characteristics of providers across the counties of Pennsylvania, primarily using data from the 2013 Survey of Dentists and Dental Hygienists administered by the Pennsylvania Department of Health.